FAKTOR PENYEBAB PERUBAHAN FONEM KOSAKATA SERAPAN BAHASA SANSKERTA DALAM BAHASA BALI - Mita Prihantika Putri, A. A. Ayu (Humanis; Volume 10. No 1. Januari 2015, 2015)
The purpose of this writing is to find out or to know the factors that cause sound changes of the Sanskrit loan vocabulary in Balinese language. There are two theories applied, respectively the theory of Sound Change proposed by Terry Crowley (1987) and theory of Generative Transformation. Two methods chosen for collecting data are methods of observation and descriptive-contrastive. For the data analysis was applied method of translational equity with basic technique of determine separated element and the continued technique of comparison and relation. The presentation of data were both in formal and informal methods. Sanskrit data was in the written form while the data in Balinese language was taken from the spoken one. The process of phoneme change was caused by two factors namely intralingual factors and ekstralingual. Intralingual factor is a factor in the language environment, while ekstralingual factors are factors outside the language.
Keywords: loan words Sanskrit, generative transformation, and cause sound changes